(3WQI eNJUQ HGH Hf CYHjO GdOYGFi Ydi fXe CHj WjHI GdSfhSi aj GdefWbs - (3HGH Hf CYHjO GdOYGFjs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje gPG hEf GdbUO fXe eNJUQ jMhi ef GdefXb eG ai GdeNJUQ eNJUQ GdTjN GdSfhSi GdEeGe ef cd eG PcQ ajg ef eQGe eY PcQ eG JQc ajg ef dhGMb hef eajO HeMd dGFb s
(3BNQgG (B:s
(3hGSJdReJ ehLHg eJUdI ShGdH GdZjQ ef GdeJUdI hPGJi efY GdLeY hGdNdh efgG GSJdReJ eJUdGJ CQHYG s
(3GdfSNI HgG MhGTs
(3GdfSNI bUjOI cJHJ HYV YfGhjfgG HGdMHQ GdCMeQs
(3MhGTjgG edjFI HTQhMgGs
(3HgG fXGe GdJYbjHI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs